Peningkatan Hasil Belajar Siswa Kelas IV SDN 07 Silang IV Silalang dalam Materi Q.S. Al-Hujurat Ayat 13 Dengan Metode Card Sort - Dasti, Elmila (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This research aims to improve the learning outcomes of fourth-grade students at SD N 07 Silang IV Silalang in the subject of Islamic Religious Education (PAI) with the topic of Q.S Al-Hujurat verse 13 through the card sort learning method. The teaching methods previously used, such as lectures and question-and-answer sessions, were considered boring and unattractive by the students, which resulted in unsatisfactory learning outcomes. By using the card sort method, it is hoped that students will become more active in learning and better understand the material in a more enjoyable way. This study employs a Classroom Action Research (CAR) approach, which consists of two cycles, each involving planning, implementation, observation, and reflection. The results of the research show that the use of the card sort method can enhance students’ learning outcomes, create a more dynamic classroom atmosphere, and help students better grasp the concepts being taught. The learning process becomes more engaging, and students feel more comfortable and actively involved in the learning process.